Acoustical Evaluation of Café in Heritage Building at Jonker Walk, Melaka - Kok How, Desmond Lee; Che Din, Nazli (International Journal of Sustainable Construction Engineering and Technology, 2022)
All the time, café is an essential part of our daily life - a node where people socialize, work, or even where they got their inspiration of idea. Lately, there been booming of adaptive reuse of heritage buildings to become café along the Jonker Street Malacca; each café is various in size and theme. All these projects mainly to restore historical visual traits and focus on restoration through function change. Somehow, designers and planners always neglect the role of sound, which is very crucial element of our environment and daily lives when making place making. Thus, this research is aimed to investigate and evaluate the level of the acoustical performance of adaptive reuse buildings at Jonker Street Malacca. Analytical method on a computational modelling of cafe will be used for this research which involved acoustical evaluation (noise level, reverberation time, Speech Transmission Index) simulation. Few cafe types were modeled in a room acoustic simulation application with a manipulated variable of volume, sizes and ceiling height. Basic sound field properties of typical cafe types are highlighted based on the finding of the study. The generated index from variables hopefully could be used to design and evaluate café specific acoustic environments in the future.